2017
DOI: 10.1002/adsu.201700043
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Passive Nanofillers in Composite Polymer Electrolyte for Higher Performance Lithium‐Ion Batteries

Abstract: Poor ionic conductivity in gel or solid electrolytes hinders the electrochemical performance and hence applications of solid‐state lithium‐ion batteries. In this work, a simple and efficient approach to increase the ionic conductivity of gel electrolytes is reported. Composite gel polymer electrolyte (CGPE) films, consisting of poly(vinylidene fluoride‐hexafluoropropylene) as the host polymer and the trilayer polypropylene membrane as the mechanical support, are prepared using charge‐modified acidic TiO2 and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…The Mg(OH) 2 ceramic particles were also incorporated into PVDF-HFP-based GPE, which enhanced flame-retardant properties and ionic conductivities of electrolyte [30] . To reduce the aggregation of fillers, a charge-modified acidic TiO 2 and basic SiO 2 nanoparticles were introduced into composite GPE (CGPE) consisting of PVDF-HFP as the host polymer and the tri-layer polypropylene membrane as the mechanical support [31] . A maximum ionic conductivities of 1.56 × 10 −3 S cm −1 was achieved in acidic CGPE.…”
Section: The Gpe Based On Pvdf or Pvdf-hfpmentioning
confidence: 99%
“…The Mg(OH) 2 ceramic particles were also incorporated into PVDF-HFP-based GPE, which enhanced flame-retardant properties and ionic conductivities of electrolyte [30] . To reduce the aggregation of fillers, a charge-modified acidic TiO 2 and basic SiO 2 nanoparticles were introduced into composite GPE (CGPE) consisting of PVDF-HFP as the host polymer and the tri-layer polypropylene membrane as the mechanical support [31] . A maximum ionic conductivities of 1.56 × 10 −3 S cm −1 was achieved in acidic CGPE.…”
Section: The Gpe Based On Pvdf or Pvdf-hfpmentioning
confidence: 99%
“…Clean and convenient lithium ion batteries (LIBs) have been widely used in most aspects of people’s lives to address the energy shortages, environmental pollution, and other issues gradually highlighted. High security is at the forefront in their many performance requirements except high energy density and good cycle performance for LIBs. At present, the carbonate-based volatile and flammable liquid electrolytes suffer from drawbacks such as leakage and flammability, causing explosion and other safety risks. Solid electrolytes are well-known as high safety and prompt the development as a hot spot. ,, However, the major challenge to realize practical application of the all-solid-state battery is the poor contact/adhesion at the solid electrolyte-electrode. The GPEs are generally prepared by swelling the liquid electrolyte in the polymer matrix, , which can take into account both important merits of the above two types of electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Nevertheless, the metal dendrites formed in liquid electrolyte systems can penetrate the polymer separators, which can lead to serious and sporadic safety issues in long-term cycling applications. [5][6][7] All-solid-state Li-ion batteries, where the ammable liquid electrolyte is replaced by solid state electrolytes, offer the possibility to solve the safety issues of traditional Li-ion batteries arising from the leakage of ammable organic liquid electrolytes, and in some cases a large electrochemical stability window compared to conventional organic electrolytes. [8][9][10] In past studies, many kinds of crystalline lithium solid electrolyte have been reported and widely applied in solid-state batteries, such as the garnet structure Li 7 La 3 Zr 2 O 12 (LLZO), 11 the perovskite structure Li 0.5 La 0.5 TiO 3 (LLTO), 12 the LISICON structure Li 14 Zn(GeO 4 ) 4 (LZGO), 13 the NASICON structure Li 1.5 -Al 0.5 Ge 1.5 (PO 4 ) 3 (LAGP), 14,15 Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 (LATP), 16,17 and so on.…”
Section: Introductionmentioning
confidence: 99%